Book review: The Posthuman Child: Educational transformation through philosophy with picturebooks. Murris, K. - Bozalek, Vivienne (Critical Studies in Teaching and Learning, 2023)
Review of: Murris, K. 2016. The Posthuman Child: Educational transformation through philosophy with picturebooks. London and New York: Routledge.